The pathology of healing and repair. Issue 1 (January 2022) - Carr, Norman J.
Abstract: Tissues that have been damaged respond by complex interactions between haemostatic, inflammatory and immunological mechanisms. Understanding these processes is central to promoting good outcomes in clinical practice, whether the injury is due to a disease or to the surgeon's scalpel. Although there are common themes that apply throughout the body, the details vary according to the type of injury and the tissues involved. This article describes general principles of healing by regeneration and repair, then wound healing in the skin by primary and secondary intention is used to illustrate the stages of haemostasis, inflammation, proliferation and remodelling. Healing mechanisms in the central nervous system and bone are also discussed, as are complications that can result from repair processes. Factors affecting healing and repair are covered with emphasis on principles relevant to surgery.